Masculinity on Stage: Dueling in the Greek Capital, 1870–1918. Issue 1 (1st March 2019) - Vassiliadou, Dimitra
Abstract : Based on some forty duels that took place in Athens between 1870 and 1918, this article examines the different connotations middle-class dueling assumed in the political culture of the period. Drawing on newspaper articles, monographs, domestic codes of honor, legal texts, and published memoirs of duelists, it reveals the diversified character of male honor as value and emotion. Approaching dueling both as symbol and practice, the article argues that this ritualistic battle was imported to Greece against a background of fin de siècle political instability and passionate calls for territorial expansion and national integration. The duel gradually became a powerful way of influencing public opinion and the field of honor evolved into a theatrical stage for masculinity, emanating a distinct glamor: the glamor of a public figure who was prepared to lay down his life for his principles, his party, the proclamations he endorsed, and his "name."